2013
DOI: 10.1080/09540121.2013.802277
|View full text |Cite
|
Sign up to set email alerts
|

Rates and predictors of prenatal depression in women living with and without HIV

Abstract: Depression is a significant mental health and public health concern, and women living with HIV are at increased risk for depression. This risk may be especially elevated during pregnancy; however, few studies have attempted to identify rates and predictors of depression in pregnant, HIV-infected women. The purpose of the present study was to investigate rates and predictors of prenatal depression, such as history of depression, childhood sexual abuse (CSA), and social support among HIV-infected and HIV-uninfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 23 publications
(29 reference statements)
3
35
4
Order By: Relevance
“…In the same population as the present study, risk factors significantly related to prenatal depression in women with HIV were childhood sexual abuse and a history of depression (Bonacquisti et al, 2014). However, in the present study, a self-reported history of depression did not predict postpartum depression symptoms, whereas childhood sexual abuse predicted postpartum depressive symptoms only in women with HIV infection.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…In the same population as the present study, risk factors significantly related to prenatal depression in women with HIV were childhood sexual abuse and a history of depression (Bonacquisti et al, 2014). However, in the present study, a self-reported history of depression did not predict postpartum depression symptoms, whereas childhood sexual abuse predicted postpartum depressive symptoms only in women with HIV infection.…”
Section: Discussionmentioning
confidence: 49%
“…Childhood sexual abuse remains a critical experience to study among women with HIV, given its demonstrated relationship to depressive symptoms and its inherent link to trauma, including such responses as posttraumatic stress disorder and symptoms (Villar-Loubet et al, 2014). In addition, women with HIV have been found to perceive lower levels of emotional support when compared with women without HIV (Bonacquisti et al, 2014). However, in this study, perceived emotional support did not have a relationship with depressive and anxiety symptoms in the prenatal and postpartum period among women with and without HIV, when controlling for other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six postpartum depression studies had information suitable and sufficient for meta-analysis and thus were meta-analyzed. Two studies (Robertson-Blackmore et al 2013; Bonacquisti et al 2014) were counted twice as the authors observed women in both the prenatal and postpartum periods.…”
Section: Resultsmentioning
confidence: 99%
“…The seven original articles reporting on the association between maternal history of CSA and prenatal depression or depressive symptoms (Benedict et al 1999; Lang et al 2006; Lev-Wiesel and Daphna-Tekoah 2010; Bublitz and Stroud 2012; Robertson-Blackmore et al 2013; Bonacquisti et al 2014; Leeners et al 2014) were based on cross-sectional data. Five studies were from the USA, one from Germany, and one from Israel.…”
Section: Resultsmentioning
confidence: 99%